Mechanisms of transcriptional regulation of ecdysone response - M. Yu. Mazina; N. E. Vorobyeva (Вавиловский журнал генетики и селекции)
The mechanisms of ecdysone-dependent expression have been studied for many decades. Initially, the activation of individual genes under the influence of ecdysone was studied on the model of polythene chromosomes from salivary glands of Drosophila melanogaster. These works helped to investigate the many aspects of the Drosophila development. They also revealed plenty of valuable information regarding the fundamental mechanisms controlling the genes’ work. Many years ago, a model describing the process of gene activation by ecdysone, named after the author – Ashburner model – was proposed. This model is still considered an excellent description of the ecdysone cascade, which is implemented in the salivary glands during the formation of the Drosophila pupa. However, these days there is an opinion that the response of cells to the hormone ecdysone can develop with significant differences, depending on the type of cells. The same genes can be activated or repressed under the influence of ecdysone in different tissues. Likely, certain DNA-binding transcription factors that are involved in the ecdysonedependent response together with the EcR/Usp heterodimer are responsible for cell-type specificity. A number of transcriptional regulators involved in the ecdysone response have been described. Among them are several complexes responsible for chromatin remodeling and modification. It has been shown by various methods that ecdysone-dependent activation/repression of gene transcription develops with significant structural changes of chromatin on regulatory elements. The description of the molecular mechanism of this process, in particular, the role of individual proteins in it, as well as structural interactions between various regulatory elements is a matter of the future. This review is aimed to discuss the available information regarding the main regulators that interact with the ecdysone receptor. We provide a brief description of the regulator’s participation in the ecdysone response and links to the corresponding study. We also discuss general aspects of the mechanism of ecdysone-dependent regulation and highlight the most promising points for further research.